Management of the Mentoring Process in Vilnius City Secondary Schools - Želvys, Rimantas; Čigienė, Sonata (Pedagogika, 2016)
The importance of mentorship in the field of education is disclosed by the projects under implementation or already implemented where the activities related to the development of mentorship in the educational system of Lithuania are depicted. However, the activity of the mentor himself/herself is prevailing in the mentorship researches as well as in practice. The activity and possibilities of manager in the process of mentorship are not analyzed or analyzed only episodically. The aim of this study is to find out whether the schoolmasters manage the process of mentorship and which possibilities of it they use and to prepare recommendations for schoolmasters in the field of mentorship based on the results obtained. The following scientific problem is formulated: what are the possibilities of the managers to manage the process of mentorship as the tool to implement the aims of the organization and the effect to the employees; what would be the use of it, what are the forms of possible organization. This attitude to mentorship from the position of manager is not much analyzed until now. The aim of the study – to disclose the activity of the manager in the process of mentorship in secondary schools of Vilnius city. Tasks: 1. Describe the process of mentorship under analysis. 2. Review the possibilities and needs of the manager to use mentorship as the tool of education of employees and formation of microclimate of school. 3. Reveal the activity of the manager in the process of mentorship in secondary schools of Vilnius city. Object: the activities of managers of secondary schools of Vilnius city in the process of mentorship in 2013–2014. Hypothesis: H1 – in cases mentorship is regulated at school the results achieved are clear and can be evaluated. H2 – in cases the manager is prepared and participates in the process of mentorship the results achieved correspond to the targets set. Methods of research: analysis of scientific literature and documentation of the field of education, questionnaire, partly structural interview, data analysis, summarizing and explication. The process of mentorship and the possibilities of the manager to use it in his/her activities are described in the study. The quantitative and qualitative research revealing the spread of mentorship its forms, target group, participation of managers and attitude to the possibilities of mentorship in the secondary schools of Vilnius city. The research showed the following: • The mentorship process for the young as well as experienced employee at school is wide spread, nevertheless, the level of this activity is different; • The mentorship could be used for the development of young as well as experienced employees (in the problematic or new fields), also for the development of mentors and formation of microclimate. • Active participation of the manager in the process of the mentorship determines focused mentorship, more precise compliance of the results to the ones planned; During the research hypothesis H1 and H2 were confirmed.